Influence of pin geometry on the joint strength of CFRT-metal hybrid parts with metallic pins - Popp, Julian; Kleffel, Tobias; Drummer, Dietmar (Joining Plastics)

Influence of rivet length on joint formation on self-piercing riveting process considering further process parameters - Kappe, Fabian; Bielak, Christian Roman; Sartisson, Vadim; Bobbert, Mathias; Meschut, Gerson (ESAFORM 2021)
Driven by the CO2-emission law by the European government and the increasing costs for raw materials as well as energy, the automotive industry is increasingly using multi-material constructions. This leads to a continuous increase in the use of mechanical joining techniques and especially the self-piercing riveting is of particular importance. The reason for this is the wide range of joining possibilities as well as the high load-bearing capacities of the joints. To be able to react to changing boundary conditions, like material thickness or strength variation of the sheets, research work is crucial with regard to the increase of versatility. In this paper, a numerical study of the influences on the selfpiercing riveting process is presented. For this purpose, the influence of different process parameters such as rivet length and die depth on various quality-relevant characteristics were investigated. With the help of the design of experiment, significant influences were determined and interactions between the individual parameters are shown.

Influence of various procedures for the determination of flow curves on the predictive accuracy of numerical simulations for mechanical joining processes - Böhnke, Max; Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Materials Testing)
The predictive quality of numerical simulations for mechanical joining processes depends on the implemented material model, especially regarding the plasticity of the joining parts. Therefore, experimental material characterization processes are conducted to determine the material properties of sheet metal and generate flow curves. In this regard, there are a number of procedures which are accompanied by varying experimental efforts. This paper presents various methods of determining flow curves for HCT590X as well as EN AW-6014, including varying specimen geometries and diverse hardening laws for extrapolation procedures. The flow curves thus generated are compared considering the variety of plastic strains occurring in mechanical joining processes. The material data generated are implemented in simulation models for the joining technologies, clinching and self-piercing riveting. The influence of the varied methods on the predictive accuracy of the simulation model is analysed. The evaluation of the differing flow curves is achieved by comparing the geometric formation of the joints and the required joining forces of the processes with experimentally investigated joints.

New Approach for Versatile Self Piercing Riveting: Joining System and Auxiliary Part - Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
The increasing use of multi-material constructions lead to a continuous increase in the use of mechanical joining techniques due to the wide range of joining possibilities as well as the high load-bearing capacities of the joints. Nevertheless, the currently rigid tool systems are not able to react to changing boundary conditions, like changing the material-geometry-combination. Therefore research work is crucial with regard to versatile joining systems. In this paper, a new approach for a versatile self-piercing riveting process considering the joining system as well as the auxiliary joining part is presented.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Investigation of the influence of varying tumbling strategies on a tumbling self-piercing riveting process - Wituschek, Simon; Kappe, Fabian; Lechner, Michael (Production Engineering)

Joining with versatile joining elements formed by friction spinning - Wischer, Christian; Wiens, Eugen; Homberg, Werner (Journal of Advanced Joining Processes)

A Method for Characterization of Geometric Deviations in Clinch Points with Computed Tomography and Transient Dynamic Analysis - Köhler, Daniel; Sadeghian, Behdad; Kupfer, Robert; Troschitz, Juliane; Gude, Maik; Brosius, Alexander (Key Engineering Materials)
When joining lightweight parts of various materials, clinching is a cost efficient solution. In a production line, the quality of a clinch point is primarily controlled by measurement of dimensions, which are accessible from outside. However, methods such as visual testing and measuring the bottom thickness as well as the outer diameter are not able to deliver any information about the most significant geometrical characteristic of the clinch point, neck thickness and undercut. Furthermore, ex-situ destructive methods such as microsectioning cannot detect elastic deformations and cracks that close after unloading. In order to exceed the current limits, a new non-destructive in-situ testing method for the clinching process is necessary. This work proposes a concept to characterize clinch points in-situ by combining two complementary non-destructive methods, namely, computed tomography (CT) and ultrasonic testing. Firstly, clinch points with different geometrical characteristics are analysed experimentally using ex-situ CT to get a highly spatially resolved 3D-image of the object. In this context, highly X-ray attenuating materials enhancing the visibility of the sheet-sheet interface are investigated. Secondly, the test specimens are modelled using finite element method (FEM) and a transient dynamic analysis (TDA) is conducted to study the effect of the geometrical differences on the deformation energy and to qualify the TDA as a fast in-situ non-destructive method for characterizing clinch points at high temporal resolution.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, Benjamin; Köhler, Daniel; Vorderbrüggen, Julian; Troschitz, Juliane; Kupfer, Robert; Meschut, Gerson; Gude, Maik (Production Engineering)
Abstract Recent developments in automotive and aircraft industry towards a multi-material design pose challenges for modern joining technologies due to different mechanical properties and material compositions of various materials such as composites and metals. Therefore, mechanical joining technologies like clinching are in the focus of current research activities. For multi-material joints of metals and thermoplastic composites thermally assisted clinching processes with advanced tool concepts are well developed. The material-specific properties of fibre-reinforced thermoplastics have a significant influence on the joining process and the resulting material structure in the joining zone. For this reason, it is important to investigate these influences in detail and to understand the phenomena occurring during the joining process. Additionally, this provides the basis for a validation of a numerical simulation of such joining processes. In this paper, the material structure in a joint resulting from a thermally assisted clinching process is investigated. The joining partners are an aluminium sheet and a thermoplastic composite (organo sheet). Using computed tomography enables a three-dimensional investigation that allows a detailed analysis of the phenomena in different joining stages and in the material structure of the finished joint. Consequently, this study provides a more detailed understanding of the material behavior of thermoplastic composites during thermally assisted clinching.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

In Situ Computed Tomography—Analysis of a Single-Lap Shear Test with Clinch Points - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (Materials)
As lightweight design gains more and more attention, time and cost-efficient joining methods such as clinching are becoming more popular. A clinch point’s quality is usually determined by ex situ destructive analyses such as microsectioning. However, these methods do not yield the detection of phenomena occurring during loading such as elastic deformations and cracks that close after unloading. Alternatively, in situ computed tomography (in situ CT) can be used to investigate the loading process of clinch points. In this paper, a method for in situ CT analysis of a single-lap shear test with clinched metal sheets is presented at the example of a clinched joint with two 2 mm thick aluminum sheets. Furthermore, the potential of this method to validate numerical simulations is shown. Since the sheets’ surfaces are locally in contact with each other, the interface between both aluminum sheets and therefore the exact contour of the joining partners is difficult to identify in CT analyses. To compensate for this, the application of copper varnish between the sheets is investigated. The best in situ CT results are achieved with both sheets treated. It showed that with this treatment, in situ CT is suitable to properly observe the three-dimensional deformation behavior and to identify the failure modes.
Keywords: General Materials Science

Clinching in In-situ CT – Experimental Study on Suitable Tool Materials - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (ESAFORM 2021)
In lightweight design, clinching is a cost-efficient solution as the joint is created through localized cold-forming of the joining parts. A clinch point’s quality is usually assessed using ex-situ destructive testing methods. These, however, are unable to detect phenomena immediately during the joining process. For instance, elastic deformations reverse and cracks close after unloading. In-situ methods such as the force-displacement evaluation are used to control a clinching process, though deviations in the clinch point geometry cannot be derived with this method. To overcome these limitations, the clinching process can be investigated using in-situ computed tomography (in-situ CT). However, a clinching tool made of steel would cause strong artefacts and a high attenuation in the CT measurement, reducing the significance of this method. Additionally, when joining parts of the same material, the sheet-sheet interface is hardly detectable. This work aims at identifying, firstly, tool materials that allow artefact-reduced CT measurements during clinching, and, secondly, radiopaque materials that can be applied between the joining parts to enhance the detectability of the sheet-sheet interface. Therefore, both CT-suitable tool materials and radiopaque materials are selected and experimentally investigated. In the clinching process, two aluminium sheets with radiopaque material in between are clinched in a single-step (rotationally symmetric joint without cut section). It is shown that e.g. silicon nitride is suited as tool material and a tin layer is suitable to enhance the detectability of the sheet-sheet interface.

Characterisation of lateral offsets in clinch points with computed tomography and transient dynamic analysis - Köhler, D.; Sadeghian, B.; Troschitz, J.; Kupfer, R.; Gude, M.; Brosius, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Investigation of Clinched Joints – A Finite Element Simulation of a Non-destructive Approach - Sadeghian, B.; Guilleaume, C.; Lafarge, R.; Brosius, A. (Lecture Notes in Production Engineering)

Experimental and Numerical Studies on the Deformation of a Flexible Wire in an Injection Moulding Process - Köhler, D.; Gröger, B.; Kupfer, R.; Hornig, A.; Gude, M. (Procedia Manufacturing)

Clinching in in-situ CT—A numerical study on suitable tool materials - Köhler, D.; Kupfer, R.; Gude, M. (Journal of Advanced Joining Processes)

Potential of Joining Dissimilar Materials by Cold Formed Pin-Structures - Kraus, M.; Merklein, M. (Journal of Materials Processing Technology)

Test Method for Friction Characterization of Rivets - Wituschek, S.; Kuball, C. M.; Merklein, M.; Lechner, M. (Defect and Diffusion Forum)

Investigation of influencing parameters on the joint formation of the self-piercing riveting process - Kappe, Fabian; Wituschek, Simon; Lechner, Michael; Bobbert, Mathias; Meschut, Gerson; Merklein, Marion

Joining with Versatile Friction-Spun Joint Connectors - Rostek, Tim; Wiens, Eugen; Homberg, Werner (Procedia Manufacturing)

Clinching in in-situ CT—A numerical study on suitable tool materials - Köhler, Daniel; Kupfer, Robert; Gude, Maik (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Mechanical joining without auxiliary element by cold formed pins for multi-material-systems - Kraus, M.; Frey, P.; Kleffel, T.; Drummer, D.; Merklein, M. (AIP Conference Proceedings)